PRUDENCE MEMODERASI PENGARUH CAPITAL INTENSITY, KOMPENSASI EKSEKUTIF DAN FINANCIAL DISTRESS TERHADAP TAX AVOIDANCE - Fitria Herlina; Iin Rosini; Nofryanti (Jurnal Riset Terapan Akuntansi, 2026)
This study examines the influence of capital intensity, executive compensation, and financial distress on tax avoidance, with accounting conservatism as a moderating variable, in consumer cyclical sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The research is motivated by inconsistent findings in previous studies and the increasing prevalence of tax avoidance practices that impact state revenue. A quantitative approach was employed using secondary financial statement data, analyzed through panel data regression and Moderated Regression Analysis (MRA). The results show that capital intensity, executive compensation, and financial distress have a significant effect on tax avoidance. In addition, accounting conservatism is proven to moderate the relationships between capital intensity, executive compensation, financial distress, and tax avoidance, serving as a quasi moderator. Overall, this study provides empirical evidence on how corporate financial characteristics and conservative reporting practices interact in influencing tax avoidance behavior. Keywords: Capital, Kompensasion, Tax, Financial, Konservatisme.